Distinctive features of technical vocabulary and shipbuilding terminology acquisition in chinese didactic environment - Chernitskii, V. B.; Movchan, L. S.; Ksilai Zhienh; Черницький, В. Б.; Мовчан, Л. С.; Ксілаї Жєнг (My University, 2014)
Issues concerning students’ masterіng general English scientific and technical terminology in the Chinese didactic environment has been studied
Особливості навчання загально технічній лексиці і суднобудівної термінології в китайському дидактичному середовищі
Chernitskii, V. B. Distinctive features of technical vocabulary and shipbuilding terminology acquisition in chinese didactic environment = Особливості навчання загально технічній лексиці і суднобудівної термінології в китайському дидактичному середовищі / V. B. Chernitskii, L. S. Movchan, Ksilai Zhienh // Гуманіт. вісн. НУК. – Миколаїв : НУК, 2014. – Вип. 7. – С. 49–51.
Keywords: еnglish borrowings; shipbuilding terminology; Content and Language Integrated Learning (CLIL); lexicographic support; англійські запозичення; суднобудівна термінологія; інтегроване вивчення іноземної мови на матеріалі змісту спеціальних дисциплін (CLIL); лексикографічна підтримка